Prākr̥ta-Hindī śabdakośa - Jaina, Udayacanda. (Nyū Bhāratīya Buka Kôrporeśana, 2005)
Dictionary of Prakrit languages.
Dictionary of Prakrit languages.
Prakrit and Hindi.
Keywords: Prakrit languages / Dictionaries / Hindi.